Using the Patch-Clamp technique to shed light on ion channels structure, function and pharmacology - Gualdani, Roberta (Premio Tesi di Dottorato, 2013)
Ion channels are membrane proteins that selectively allow ions to flow down their electrochemical gradient across the cellular membrane. They localize in both plasma and intracellular membranes and regulate a variety of functions such as neuronal excitability, heartbeat, muscle contraction and hormones release. Thus, understanding the molecular mechanism of ion channels function and regulation is one of the key goals of modern Biophysics. During my PhD thesis, by combining patch-clamp measurements with site-direct mutagenesis, fluorophore labeling experiments and pharmacological assays, I explored some functional and structural properties of different ion transporters: the Na+/Ca2+ exchanger (NCX); the large conductance Ca2+-voltage activated K+ channel (BK) channel; the human Transient receptor potential, member A1 (TRPA1) channel.